A 28-Year-Old Man With Mediastinal Seminoma Treated With BEP - Rizki, Agustinus; Wulandari, Laksmi (Folia Medica Indonesiana, 2021)
Highlight: • A 28-year-old male suffered chylothorax and mediastinal seminoma. • The patient received bleomycin, etoposide and cisplatin chemotherapy for the management of mediastinal seminomas but he died beforeundergoing 5th cycle chemotherapy. Abstract: Seminoma is a type of germ cell tumor. In this case presentation, a rare primary germ cell tumor was reported in the form of mediastinal seminoma. A 28-year-old man with symptoms of shortness of breath, chest pain, swelling in the right upper extremity, enlarged lymph nodes in the colli region. Thoracic physical examination revealed signs of pleural fluid in the right hemithorax. After obtaining the results of radiological and pathological investigations, a mediastinal mass was obtained, then BEP chemotherapy was given. After 3 cycles of chemotherapy, a partial response was obtained. Patients with mediastinal seminoma treated with BEP base chemotherapy gave a partial response.